DEPRECIATION POLICY UNDER CHANGING PRICE LEVELS. - Edwards, Edgar O. (The Accounting Review, 1954)
The purpose of this paper is to suggest that both current cost and adjusted historical cost have an accounting role to play, that these techniques are essentially complementary rather than competitive, and that actual cost at the time of replacement a concept which properly should be abandoned for depreciation purposes. In the process of establishing these points one possible approach to depreciation under changing price levels will be developed which utilizes both the current fixed asset cost ("current cost") and historic cost adjusted by a general price index ("purchasing power cost") as bases for depreciation. This approach, considerably simplified for expositional purposes, has as its primary aim a meaningful statement of economic profit, but appears to have advantages for computing taxable profit and taxable gains, and for making replacement, properly considered, possible. The application of this technique would involve certain practical difficulties but they are not insurmountable.